Buying and selling the environment : how to design and implement a PES scheme - Scheufele, Gabriela; Bennett, Jeff (Academic Press, an imprint of Elsevier, 2019)
Buying and Selling the Environment: How to Design and Implement a PES Scheme provides a guide to the design and implementation of PES schemes that 'mimic' market processes, including three key elements: the estimation of the demand for environmental services, an understanding of the costs of supply, and how to predict the productivity of actions taken. This book will act as an instructional manual for practitioners, policymakers and their advisors in government and non-government organizations. Users will find a step-by-step demonstration based on firsthand experiences gained through a PES application at two case study sites. Finally, the book presents research in applied economics and bio-physical modeling.